Pemasaran Vendor Wedding Organizer Melalui Aplikasi Moore Berbasis Web Mobile Menggunakan Metode Agile - Muhammad Nurhadi; Sulistyo Dwi Sancoko (Journal of Information System Research (JOSH), 2025)
The wedding industry in Indonesia has undergone a significant transformation thanks to technological advancements and changing consumer behavior. Today, brides-to-be are increasingly utilizing digital platforms to search and book wedding services. Many vendors still manage the booking system conventionally. The booking system at vendors still uses regular telephone calls so there are often errors in recording bookings because the vendors often forget to record the booking schedule in the ledger. Promotional activities are also still very limited. This research aims to develop a mobile web-based application that facilitates wedding vendors in offering their services and products more efficiently. This application is designed to overcome various challenges faced by vendors, such as difficulties in promoting vendors to prospective brides, managing bookings, communicating with clients, and improving operational efficiency to achieve client satisfaction with the services provided. The application development involved collecting wedding package data, product data (such as physical souvenirs and invitations), system design, technology selection, and implementation and evaluation strategies. The technologies used include React JS for web application development and React Native for mobile applications, both using the JavaScript programming language. The database uses MongoDB, with the support of platforms such as Stripe as a payment gateway. The software development method applied is Agile, to ensure flexibility and responsiveness to user needs. The interim result of this research is an application that provides a source of information for prospective brides related to vendors of wedding organizer products and services with a wide scope. In addition, the Moore App has been tested by 30 respondents with an average success rate of 100%, indicating that all features function properly according to user needs and established specifications.